Assessing Borrowing: The Case of Gurdjieff - Azize, Joseph (Aries, 2020)
The history of esoteric currents cannot be intrinsically closed to scholarly research and query. Here, we shall examine just one question: that of methodology in examining the sources of esoteric systems. We shall take but one case study: that of Tobias Churton's recent book-length efforts to "deconstruct" George Ivanovich Gurdjieff and his teaching. Like others before him, he traces diverse aspects of Gurdjieff's teaching to different sources, viewing Gurdjieff as a synthesiser, who disguised his debt to Western Esotericism and presented it as his "Fourth Way". How can such a theory be evaluated? Is it possible to draw up a canon of principles for assessing borrowing? In evaluating borrowing, does the whole of a teaching possess a significance over and above the parts? What is the significance of the phenomenon of borrowing? After noting some results of research on inter-cultural borrowings in ancient mythology, I make suggestions for sound methodology.